Synthesis Of Silver Nanoparticles (Agnp) From The Extract Of Kemloko Fruit (Phyllantus Emblica L.) - Mukhlisa, Ida; Masfria, Masfria; Sumaiyah, Sumaiyah (International Journal of Science, Technology & Management, 2022)
Nanoparticles are nano-sized materials that are widely used because they have many advantages and very beneficial benefits. One method of making nanoparticles biologically. In the process of chemically synthesizing silver nanoparticles, nanomaterials are toxic and not environmentally friendly. So, other options are used, such as biological synthesis with natural materials as reducing catalysts and plant extract bioreductors that can reduce the amount of dangerous materials in the waste. This study aims to make nanoparticles from kemloko ethanol extract with biological methods. Extraction was carried out by the maceration method and synthesis of silver nanoparticles by a biological method with functional group analysis characteristics using FTIR. The results of this study indicate that these nanoparticles indicate that silver nanoparticles can be synthesized biologically for silver nanoparticles and the FTIRcharacteristic results show that silver nanoparticles contain OH, C=O, N=O, C-O, and C-H groups.